2021
DOI: 10.1177/1934578x211034387
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of Anti-Lung Cancer and Anti-COVID-19 Effects using Fermented Black Color Ginseng Extract

Abstract: Ginseng is known as the “king” of herbal plants and has been used widely in Asia for centuries. Ginseng contains active saponins, including protopanaxadiols, protopanaxatriols, and other compounds. There are many methods for processing ginseng, such as steaming, fermentation, expansion, and conversion of active compounds, which can improve its biological activity. In this study, we investigated the cytotoxic and oxidative effects of fermented black color ginseng (FBCG), black ginseng (BG), and white ginseng (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This study has also found that KRG could inhibit the upregulation of inflammatory signal of Mitogen-activated protein kinases (MAPK) [ 47 ]. In lung cancer cell line (A549), fermented black color ginseng has shown potential anti-lung cancer properties, furthermore it has inhibited the replication of SARS-CoV-2-infected Vero E6 cell and reduced the amount of viral RNA copies in the extracellular environment [ 48 ]. In another study, virus infected mice fed with ginseng extract for 180 days showed lower viral titers in the lung compared to control.…”
Section: Ginseng and Ginsenoside On Cardiac And Pulmonary Injurymentioning
confidence: 99%
“…This study has also found that KRG could inhibit the upregulation of inflammatory signal of Mitogen-activated protein kinases (MAPK) [ 47 ]. In lung cancer cell line (A549), fermented black color ginseng has shown potential anti-lung cancer properties, furthermore it has inhibited the replication of SARS-CoV-2-infected Vero E6 cell and reduced the amount of viral RNA copies in the extracellular environment [ 48 ]. In another study, virus infected mice fed with ginseng extract for 180 days showed lower viral titers in the lung compared to control.…”
Section: Ginseng and Ginsenoside On Cardiac And Pulmonary Injurymentioning
confidence: 99%
“…More than 150 identified ginsenosides significantly treat various conditions, including cancer, inflammation, cardiovascular diseases, autoimmune disorders, and metabolic conditions [ [37] , [38] , [39] ]. Recent studies have explored the antiviral efficacy of fermented black ginseng extract in inhibiting SARS-CoV-2 replication and reducing viral RNA copies [ 40 ]. Other studies have also investigated the antiviral potential of ginseng against SARS-CoV-2 [ [41] , [42] , [43] , [44] , [45] , [46] ].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 A recent study has investigated the anti-viral efficacy of the fermented black ginseng extract, which inhibits the replication of this virus strain in the SARS-CoV-2 infected Vero E6 cell, but also reduces the number of viral RNA copies in the extracellular environment. 24 Additionally, ginsenosides are reported to mimic the action of steroids in binding and explicating similar activities via binding to glucocorticoid receptors. Ginsenoside Rg1 is a natural plant compound with structural similarity to classical glucocorticoids.…”
Section: Introductionmentioning
confidence: 99%